THE MEDIATING ROLE FOR IMPROVING MARKETING PERFORMANCE - Ulfa, Devita Nurul; Murwatiningsih, Murwatiningsih (Management Analysis Journal, 2020)
This research aims to examine the effect of marketing knowledge competence and customer orientation on performance of marketing toward marketing capabilities. The population data in  this research is the hawkers of Tuin Van Java centre in Magelang City. The total sample is 127 respondents. This research using a saturated sampling. The data analysis  method in this research using descriptive analysis, regression analysis, and path analysis with IBM SPSS versi 21. The research result shows that marketing knowledge competence and customer orientation had positive and significant influence on marketing performance through marketing capabilities. marketing capabilities are also able to mediate the effect of marketing knowledge competence and customer orientation toward marketing performance.